Konsep Dasar Kewirausahaan : Fondasi Teoritis dalam Membangun Jiwa Wirausaha di Era Modern - Natasya Ika Suryaningsih; Agung Winarno; Wening Patmi Rahayu (Universitas 45 Surabaya, 2026)
This conceptual article examines the foundational dimensions of entrepreneurship by integrating theoretical perspectives on entrepreneurial principles, character, and mindset within the context of modern economic and technological transformation. The study is motivated by the increasing relevance of entrepreneurship in fostering innovation, economic resilience, and social value creation. The objective of this research is to formulate a comprehensive theoretical understanding of how fundamental entrepreneurial concepts shape entrepreneurial readiness and behavior in contemporary environments. Using a literature review approach, data were collected from academic journals, scholarly books, and recent review articles relevant to entrepreneurial opportunity identification, business planning, innovation, value creation, psychological capital, and digital-era entrepreneurship. The analytical technique employed involved theory synthesis, conceptual comparison, and deductive conclusion-building based on the existing literature. The findings show that entrepreneurial principles—such as opportunity orientation, creativity, innovation, and value creation—provide a conceptual direction for entrepreneurial action. Entrepreneurial character, including resilience, self-management, optimism, adaptability, and proactive behavior, strengthens the psychological foundation needed to navigate uncertainty. Meanwhile, the entrepreneurial mindset emerges as a dynamic cognitive framework shaped through experience, iterative learning, and environmental stimuli, enabling individuals to interpret market changes as opportunities. In the modern era, digital technologies, globalization, and social entrepreneurship further expand the landscape of entrepreneurial practice. The study concludes that these three core components—principles, character, and mindset—form an interconnected framework essential for entrepreneurship development. Practically, the article highlights the importance of integrating experiential learning, technological literacy, and character-building approaches in entrepreneurship education. The study also acknowledges its limitation as a conceptual work and recommends future empirical research to validate the relationships among these entrepreneurial dimensions across diverse contexts.